2017
DOI: 10.1016/j.amsu.2017.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Improving antibiotic prophylaxis in gastrointestinal surgery patients: A quality improvement project

Abstract: BackgroundA surgical site infection (SSI) is a frequent complication following gastrointestinal surgery, but the careful selection and administration of prophylactic antibiotics can reduce the risk. The aim of this study was to develop a package of interventions that could be used to improve surgical antibiotic prophylaxis (SAP) at our institution.MethodsA pre-post quality improvement project at a private hospital in Saudi Arabia was conducted between January 2014 until July 2016. A multidisciplinary team was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 29 publications
2
16
1
2
Order By: Relevance
“…This finding was similar to that seen in our study wherein concern for serious or severe infection prompted surgeons to unnecessarily choose broader spectrum antibiotics, thereby placing patients at risk for antibiotic resistance and fungal infections. The use of clinical decision support pathways and order sets that are incorporated into the electronic medical record may help guide antibiotic selection and prevent antibiotic overuse [14,19]. These order sets should be developed with the input of pharmacists and include optimal dosing for the chosen antibiotic, thereby potentially overcoming the AP dosing issues noted in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was similar to that seen in our study wherein concern for serious or severe infection prompted surgeons to unnecessarily choose broader spectrum antibiotics, thereby placing patients at risk for antibiotic resistance and fungal infections. The use of clinical decision support pathways and order sets that are incorporated into the electronic medical record may help guide antibiotic selection and prevent antibiotic overuse [14,19]. These order sets should be developed with the input of pharmacists and include optimal dosing for the chosen antibiotic, thereby potentially overcoming the AP dosing issues noted in our study.…”
Section: Discussionmentioning
confidence: 99%
“…These order sets should be developed with the input of pharmacists and include optimal dosing for the chosen antibiotic, thereby potentially overcoming the AP dosing issues noted in our study. A multi-disciplinary approach including pharmacy, surgeons, nursing, and anesthesia for the development of the clinical decision support pathway may help to shed light on different perspectives of patient care and hold all members of the patient care team accountable for ensuring appropriate use of AP [14,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…What is currently being done to address SAP internationally? Successful interventions to improve SAP prescribing include studies in both resource limited and resource rich settings, and include the collaborative development of guidelines, data collection on compliance with guidelines and quality assurance cycles with audit and direct prescriber feedback [7,[9][10][11]. However, in both contexts suboptimal SAP prescribing persists, and barriers to implementation are evident, including the enduring belief within surgery regarding the benefit of post-operative SAP administration to prevent SSI [10,12,13].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The main characteristics of all 40 included studies are presented in Table 2. Twenty-five studies were performed in the US [36, 37, 39, 45-52, 55, 56, 58-60, 62, 63, 65, 67, 69-73], two each in Australia [34,54], Canada [41,42], the Netherlands [38,44], Spain [40,64], and the UK [35,66], and one each in Germany [68], Saudi Arabia [53], Singapore [57], Switzerland [61], and Qatar [43]. Thirty-six studies were single-center studies, and four studies were performed in more than one hospital [50,65,66,69].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…In some of these studies, the compliance rates were reported in narrative or graphical form only, which made it difficult to determine the exact rates. In addition, from those studies that reported explicit baseline and cohort compliance rates, 13 studies reported rates for individual measures, while 7 presented global rates for all clinical measures [35,38,42,53,54,62,64]; only two studies reported both types of rates [34,63]. Thus, further analyses on the associations between implementation interventions and compliance with clinical interventions are omitted.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%